Thermodynamics of expanded fluid metals based on the concept of clusters and solids. Issue 1 (20th February 2019) - Kitamura, Hikaru
Abstract : Nonempirical theories on the thermodynamics of expanded fluid metals are presented, with a particular emphasis on the treatment of interatomic many‐body interactions with the aid of the concept of clusters and solids. Statistical methods are combined with the hard‐sphere or compressible lattice‐gas model to take a configurational average of the atoms analytically. The resultant free energy or the grand potential is minimized by the variational principle to compute the equation of state without introducing adjustable parameters. As a numerical example, the gas‐liquid coexistence curve of fluid rubidium is calculated by the cluster variation method.